Age and sex differences in in-air vocalization characteristics of spotted seal pups from newborn to 1 year old in captivity - Zhang, Peijun; Yang, Liangliang; Han, Jiabo; Yang, Yong; Lu, Zhichuang; Li, Songhai (Frontiers in Marine Science, 2022)
Acoustic parameters of spotted seals (Phoca largha), including the duration, peak frequency, and peak-to-peak source level, are reported to vary between different ages and sexes; however, to our knowledge, the vocal ontogeny of the spotted seal from newborn to one year old is yet to be studied. In the present study, we recorded and analyzed vocalizations of human-cared spotted seals from the Liaodong Bay colony from newborn to one year old, aiming to document the first-year development of seal vocalizations. We divided the spotted seal pups into four age groups (i.e., 1-3-month, 4-6-month, 7-9-month, and 10-12-month groups) for both sexes. The results show significant differences in sex patterns in sound parameters in terms of duration, peak frequency, and peak-to-peak source level. The vocalizations of female seal pups were longer in duration but lower in peak frequency and peak-to-peak source level than those of male pups. All three sound parameters were significantly different across different age groups. Specifically, the 1-3-month group had significantly lower values in duration, peak frequency, and peak-to-peak source level than the three other age groups. The 10-12-month group had significantly higher values in duration and peak-to-peak source level than the three other age groups. Our results also indicate a sex-specific development pattern of seal vocalizations from one year old until sexual maturity. Our findings will benefit the evaluation of anthropogenic noise impacts on spotted seal pups and further conservation of the seal population.